Peningkatan Kemampuan Manajemen Pelaku UMKM Dalam Menghadapi Persaingan Pasar - Bustam Bustam; Hasbiyadi Hasbiyadi; Susiana Muchtar; Mustafa Gani; Wahyudi Wahyudi; Masyita Masyita; Muh. Umar Data; Nurlaely Razak (Universitas Maritim AMNI Semarang, 2023)
One of the development priorities in the Government Work Plan (RKP) is the development of Micro, Small and Medium Enterprises (MSMEs). This is based on the fact that MSMEs have contributed a lot to the national economy. The development of Micro, Small and Medium Enterprises (MSMEs) is very strategic, because of its great potential in driving community economic activities, as well as being the main source of income for most people in improving their standard of living. well-being. (Ariani et al, 2017). Micro, Small and Medium Enterprises (MSMEs) have become an important part of the national economic system capable of accelerating economic growth through the mission of opening business and employment opportunities, increasing people's income, playing a role in increasing foreign exchange earnings and strengthening the structure of the national economy (Hafni & Rozali, 2017).One of the development priorities in the Government Work Plan (RKP) is the development of Micro, Small and Medium Enterprises (MSMEs). This is based on the fact that MSMEs have contributed a lot to the national economy. The development of Micro, Small and Medium Enterprises (MSMEs) is very strategic, because of its great potential in driving community economic activities, as well as being the main source of income for most people in improving their standard of living. well-being. (Ariani et al, 2017). Micro, Small and Medium Enterprises (MSMEs) have become an important part of the national economic system capable of accelerating economic growth through the mission of opening business and employment opportunities, increasing people's income, playing a role in increasing foreign exchange earnings and strengthening the structure of the national economy (Hafni & Rozali, 2017).